2022
DOI: 10.1016/j.lanwpc.2021.100336
|View full text |Cite
|
Sign up to set email alerts
|

The mortality trends of falls among the elderly adults in the mainland of China, 2013—2020: A population-based study through the National Disease Surveillance Points system

Abstract: Background Fall in elderly is a major public health problem. Characterizing trends in fall mortality in different subpopulations could help identifying the needs and developing preventive program for target groups. Here we evaluated the trends of fall-related deaths in Chinese mainland among adults aged ≥60 years specific in sex, age, and provinces, to measure the change in this mortality rate between 2013 and 2020, and to explore the underlying factors influencing this change.Methods Mortality data were retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…The results suggest that this trend increased in the analyzed period, with an increase rate of 5.45% per year being observed. A recent study carried out in China by analysis of trends showed that, between 2013 and 2020, the mortality rate from falls in older adults also had an upward trend 37 . Studies conducted in other countries, such as the United States of America, Canada, and Spain, also demonstrated an increasing trend in mortality from falls in older people 6,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest that this trend increased in the analyzed period, with an increase rate of 5.45% per year being observed. A recent study carried out in China by analysis of trends showed that, between 2013 and 2020, the mortality rate from falls in older adults also had an upward trend 37 . Studies conducted in other countries, such as the United States of America, Canada, and Spain, also demonstrated an increasing trend in mortality from falls in older people 6,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…Os resultados sugerem que essa tendência foi crescente no período analisado, sendo observada taxa de incremento de 5,45% ao ano. Pesquisa recente realizada na China por meio da análise de tendências demonstrou que, entre os anos de 2013 e 2020, a taxa de mortalidade por queda em idosos também teve tendência ascendente 37 . Estudos realizados em outros países, como Estados Unidos, Canadá e Espanha, também revelaram a tendência crescente da mortalidade por quedas em idosos 6,38,39 .…”
Section: Discussionunclassified
“…With the accelerating rate of population aging in China, the proportion of the elderly population is also increasing. 17 By the end of 2019, the number of people aged 60 years and older in China was 254 million, accounting for 18.1% of the total population; meanwhile, the population aged 60 and above had reached 264 million, accounting for 18.7% of the total population by the end of 2020. 18 , 19 Along with the progress of population aging, various social problems were emerging especially the increase in medical issues.…”
Section: Discussionmentioning
confidence: 99%